Standarisasi Parameter Spesifik Ekstrak Etanol Daun Pegagan (Centella asiatica L.) Sebagai Antidiabetes - Fahmi Sadik; A. Rifqah Amalia Anwar (Journal Syifa Sciences and Clinical Research, 2022)
Gotu kola (Centella asiatica L.) is empirically used as a medicinal plant and scientifically it can be used to treat various diseases based on the results of the Scientification of Herbal Medicine. Gotu kola leaf (Centella asiatica L.) is one of the potential medicinal plants that can be used as herbal medicine because it contains various kinds of nutritious compounds. Because of the many benefits of gotu kola leaves, it is necessary to standardize the extract to ensure the quality associated with the identity substance, and the composition of the chemical content whose specifications are stated in the monograph as a quality requirement listed in Materia Medika Indonesia. Standardization includes organoleptic test, identification of chemical content, determination of water soluble extract content, ethanol soluble extract content and other tests, namely seeing the activity of gotu kola as an antidiabetic. The results and data on the characteristics of the specific parameters indicated that the extracts made had met the requirements of the herbal pharmacopoeia, which means that the ethanolic extract of gotu kola had met the standards, and based on activity testing it was known that the leaf of gotu kola (Centella asiatica L.) was efficacious as antidiabetic.